Leader-member exchange theory in Pejabat Tanah Batu Pahat / Nur Fatin Shahlan - Shahlan, Nur Fatin (2014)
The relationship between a leader and the employees is important to apply it in the organization. In processing the good leader-member exchange, the leader will apply the good leadership style to their employees or followers. The relationship will become high or low relationship depends on the value and style of leadership that the leaders apply in the organization. The present study examines the implementation of the three elements which are relationship, loyalty, and contribution. A total of population at Pejabat Tanah Batu Pahat for this study is 50 respondents and only 44 respondents have been chosen as a sample size. This finding shows that contribution variables is the most significant element for the LMX theory, moreover the loyalty variables is the low significant element because of the employees in Pejabat Tanah Batu Pahat believe that their leader must show and use their ability and skills to handling their organization.